Intra- and Interspecific Variation in Sexual Dimorphism Patterns of Mud Crab Genus Scylla Along the Equatorial Region - Waiho, Khor; Ikhwanuddin, Mhd; Abualreesh, Muyassar H.; Shu-Chien, Alexander Chong; Ishak, Sairatul Dahlianis; Jalilah, Mohamad; Azmie, Ghazali; Fazhan, Hanafiah (Frontiers in Marine Science, 2021)
Sexual dimorphism is generally obvious in brachyurans and sexual dimorphism between species is of higher degree to allow separation of trophic niches compared to the lower intraspecific variations between sexes. Mud crab genus Scylla are distributed along Indo-West Pacific region, and species within this genus often exhibit overlapping niches and similar external morphologies. This study compared the intra- and interspecific sexual dimorphism patterns of three sympatric Scylla species from four distinct geographical locations along the equatorial region based on 24 morphometric characters. The consistency of sexual dimorphism patterns between locations was higher than between species. However, reproduction-related characters such as cheliped dimensions and abdomen width exhibited similar sexual dimorphism patterns across species. Discriminant function analysis based on the 23 morphometric ratios revealed the morphometric intraspecific divergence in all three Scylla species from Asajaya Mangrove Forest. The cause for this regional intraspecific differentiation of mud crabs from Asajaya Mangrove Forest remains unknown.